Caracterização do perfil motor de escolares com transtorno autístico - Okuda, Paola Matiko Martins [UNESP]; Misquiatti, Andréa Regina Nunes [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2010)
Thematic focus: The motor abnormalities may be part of so-called comorbidities that can coexist with autistic disorder. Objective: To characterize the motor profile of students with autistic disorder. Method: the study included six children with years and 9 months. After signing the consent form by parents or guardians, the students were submitted to the Motor Development Scale for assessment of fine motor, gross motor performance, balance, body scheme, spatial organization, temporal organization and laterality. Results: The results revealed a significant difference between the motor age and chronological age. According to the classification of the Scale of Motor Development, students in this study showed motor development lower than expected for age. Conclusion: The students with autistic disorder in this study presented a profile of Developmental Coordination Disorder in comorbidity, showing that participants of this research presented difficulties in activities that required skills such as handwriting. Thus, motor and psychomotor needs of these students were focused on educational and clinical environment to reduce the impact of behavioral and social manifestations.

Foco temático: As alterações motoras podem fazer parte das chamadas comorbidades que podem coexistir com o transtorno autístico. Objetivo: caracterizar o perfil motor de escolares com espectro autístico. Método: participaram deste estudo 6 escolares com transtorno autístico do ensino fundamental, do gênero masculino, com idades variando entre 5 anos e 5 meses e 10 anos e 9 meses. Após a assinatura do termo de consentimento pelos pais ou responsá- veis, os escolares foram submetidos à aplicação da Escala de Desenvolvimento Motor para avaliação da motricidade fina, motricidade global, equilíbrio, esquema corporal, organização espacial, organização temporal e lateralidade. Resultados: Os resultados revelaram diferença significante entre a idade motora e a idade cronológica. Conforme a classificação da Escala do Desenvolvimento Motor, os escolares deste estudo apresentaram desenvolvimento motor inferior ao esperado para a idade. Conclusão: Os escolares com transtorno autístico deste estudo apresentam quadro de Transtorno do Desenvolvimento da Coordenação em comorbidade, demonstrando que os participantes desta pesquisa apresentam dificuldades em atividades que exijam destreza como a grafia. Assim, as necessidades motoras e psicomotoras desses escolares são enfocadas no ambiente clínico e educacional para diminuir o impacto das manifestações comportamentais e sociais.
Caracterization of the motor profile of students with autistic disorder